1983
DOI: 10.1021/jo00165a011
|View full text |Cite
|
Sign up to set email alerts
|

Binding profiles for oligoethylene glycols and oligoethylene glycol monomethyl ethers and an assessment of their abilities to catalyze phase-transfer reactions

Abstract: Supplementary Material Available: Anisotropic temperature parameters, the positional and isotropic temperature parameters of the hydrogen atoms, tables of bond distances, bond angles, and torsion angles (partially) in comparison with values of compound Id, and a description of the crystal packing together with a stereoscopic representation (4 pages). Ordering information is given on any current masthead page. The lists of observed and calculated structure factors are available from A. Gieren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 0 publications
3
31
0
Order By: Relevance
“…Thus, the initial reaction rate will then remain at a constant value when the molecular weights of the PEGs are greater than 1500. These results, obtained from the present study are in general very consistent with those of Gokel et al [10], Ugelstad and Rokstad [24] and Yamazaki et al [28].…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Thus, the initial reaction rate will then remain at a constant value when the molecular weights of the PEGs are greater than 1500. These results, obtained from the present study are in general very consistent with those of Gokel et al [10], Ugelstad and Rokstad [24] and Yamazaki et al [28].…”
Section: Resultssupporting
confidence: 94%
“…(A) Effects of the molecular weights of PEGs Gokel et al [10] conducted experiments to study the capability of forming a complex from polyethylene and the sodium cation in a methanol solution. They found that the same quantities of complex from polyethylene glycols and the sodium cation are obtained using the same amount of PEG of various molecular weights.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They have a capability similar to crown ether compounds and are stable at high temperatures and in strong alkaline conditions and are, therefore, more in demand Neumann and Sasson, 1983;Li and Alper, 1986). Some researchers have compared polyethylene glycol and crown ethers (Gokel et al, 1983;Harris et al, 1982;Harris et al, 1985), polyethylene glycol and quaternary ammonium salts (Zupancic and Kokalj, 1981;Lee and Chang, 1978). Generally, crown ethers seem to be more similar to PEG than other phase transfer catalysts.…”
Section: Modifi Ed Ullmann Condensation Reaction Using Copper Salt Anmentioning
confidence: 99%
“…Figure 1 la Although this behavior is not trivial, it can be explained if one considers the complexation ability of a crown ether in comparison to that of an oligooxye'k ylene glycol. 23 Since the crown ether is more selective and binds ions much stronger than the glycol, the phase behavior of the mixture can be explained by considering the presence of two distinct components. One is the complexed compound 5, the other is the mixture of remaining uncomplexed 2 and 5.…”
Section: Crown-5 Endo-receptors and Their Ternary Mixture With Nacf mentioning
confidence: 99%